( n-1 ) – Reconstruction of Tournaments Mn (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
In this paper, we show that the kind of tournament Mn , which are indecomposable , then this type or tournament are (n-1) RECONSTRUCTION.